THE RELEVANT ISSUES OF CARRYING OUT THE INVESTIGATIVE ACTION – ON-SITE EXAMINATION OF TESTIMONY – IN THE CRIMINAL PROCEDURE OF LATVIA - Sumbarova, Marina (Administrative and Criminal Justice, 2017)
One of the priorities in the activity of law enforcement establishments of Latvia is the qualitative investigation of crimes. The persons, directing the process, the investigators, prosecutors, judges constantly improve their professional skills in investigating criminal proceedings. The carrying out the investigative actions without violation of norms of Criminal and procedural law, using the scientific and technical means, with the participation of specialists is the key of successful investigation of criminal proceedings in various types of crimes. The goal of the research is the examination of criminal and procedural and tactical characteristics of the investigative action – the check of testimonies on the spot in the criminal procedure of Latvia. The scientific approaches of conducting of the check of testimonies on the spot, the practical provisions of the specified investigative action are identified; additions on the improvement of the criminal and procedural law on carrying out the check of testimonies on the spot and certain tactical proposals, related to this investigative action are made.